« Tu n’as rien vu à Constantinople » : Thackeray au pays des harems - Laurent Bury (Cahiers Victoriens et Edouardiens)
In his Notes of a Journey from Cornhill to Grand Cairo, Thackeray used once again the persona of Michael Angelo Titmarsh, which he had created for Punch. The volume published in 1846 had been preceded by a series of articles in that magazine, under the title « Wandering of our Fat Contributor ». Thackeray had a personal knowledge of colonial matters, but his text is presented as the trite reflections of a blasé tourist, who constantly asserts England’s superiority. In Notes..., the reader also finds the usual Thackerayan phenomenon of split personality, the narrator and the illustrator being one and the same person. Pictures play a central part in the book, hinting at the impossible immediacy of travel writing, a genre in which the traveller’s testimony is inevitably filtered by all kinds of obstacles, as opposed to the Victorian ideal of a direct transcription of reality.